Overview of Covid-19 Patient Mortality in Gowa Regency in 2021 - Wijaya, Dian Rezki; Bujawati, Emmi (Universitas Islam Negeri Alauddin Makassar, 2025)
The Covid-19 Case Fatality Rate in the World is 2.07% and Indonesia is 3.31% as of 7 September 2021. There are 2,129 people who died from Covid-19 in South Sulawesi Province with Gowa Regency ranking 2nd with the highest number of cases. This study aims to provide an overview of the mortality of Covid-19 patients in Gowa Regency in 2020. This quantitative type of research with a descriptive design uses Secondary Data Analysis (ADS). The population is 51 people with the sampling technique using total sampling. variables in this study include age, gender, and place of residence. The results obtained are cases of death due to Covid-19 are dominant in men (64.7%), elderly people with an age range of 46-55 years (33.3%), and domiciled in Somba Opu District (54.9%). %). Further research can be done using more complex variables. Researchers recommend to the local government to maximize care for patients who are male and elderly. In addition, tighten the mobility of people in densely populated areas so that the death rate does not increase.